Homeland Consciousness in Chinese Maritime Island Science Fiction - Yuqin Jiang (Island Studies Journal)
Abstract: Chinese maritime island science fiction is an essential part of the genre, reflecting China’s historical sea-land worldview, which is deeply rooted in land-based politics and cultural identity. As a subcategory of Chinese science fiction literature, it constructs a knowledge landscape centered on the dynamic interplay between the mainland, the ocean, and the islands. This landscape is fundamentally anchored in a profound homeland consciousness. This homeland consciousness in Chinese maritime island science fiction manifests in three key narrative modes: (1) Political mode. The homeland consciousness serves as the driving force behind the use of advanced technology to safeguard national security and enhance state power. (2) Cultural mode. The homeland consciousness is envisioned as both a cultural homeland and an imagined utopia, explored through the dialectical relationship among the mainland, the ocean, and the islands. (3) Cyclical mode. The homeland consciousness embodies China’s deeply ingrained cosmological belief in the cyclical harmony of heaven and humanity, where the longing for and protection of homeland remains an enduring theme. The homeland consciousness in Chinese maritime island science fiction both engages with and transcends the conventional binary of islands and continents. It integrates oceanic islands into a new dialectical cultural framework, where they are not only the frontier guardians and pioneers of home, but also its philosophical embodiment. This perspective provides a fresh foundation for establishing a new island poetics.